The Influence of Digital Marketing on Msme Performance with Intellectual Capital and Competitive Advantage Aas Mediating Variables (Survey of Culinary MSMEs in Solo) - Rahadhini, Marjam Desma; Nadiya Fikriyatuz Zakiyah; Liony Nadia Sekar Arum (International Journal of Economics, Business, and Entrepreneurship, 2025)
Indonesia faces significant challenges in creating adequate employment opportunities, leading many people to turn to the Micro, Small, and Medium Enterprises (MSMEs) sector. MSMEs, particularly in the culinary sector, play a crucial role in driving economic growth and equitable distribution of prosperity. However, MSMEs often face challenges such as low competency, a lack of adaptation to business changes, and limited use of digital technology. Digital marketing is a crucial strategy for improving MSME performance by expanding market access and strengthening product branding. Furthermore, intellectual capital, encompassing knowledge, skills, and networks, contributes to improving MSME competitiveness and performance. Competitive advantage, based on MSME resources and capabilities, is a key factor in their success in facing global competition. This study focuses on the influence of digital marketing on the performance of culinary MSMEs in Solo, with intellectual capital and competitive advantage as mediating variables. The results are expected to provide an understanding of the importance of managing digital marketing and intellectual capital to strengthen MSME competitiveness and performance in the digital era. This study is limited to culinary MSMEs in Solo, thus requiring further research in broader business sectors and regions.